PERSPEKTIF ETIKA HINDU TERHADAP PERILAKU FLEXING PADA PENGGUNA INSTAGRAM - Ni Putu Ayu Budiartini; Srirahayu Puspawati; John Abraham Ziswan Suryosumunar (Sanjiwani: Jurnal Filsafat, 2022)
This research is directed to analyze flexing behavior in Instagram users which is widely used by all circles. This flexing behavior is a phenomenon that appears in line with the growing times. To support this research, it was studied using a Hindu ethical perspective. The Hindu ethical perspective used in this study is the teachings of Sapta Timira which is the seven darknesses that can make people fall into darkness so that they can easily forget about themselves, and where they come from. The data of this study were obtained by observation, interview and literature methods. Furthermore, the philosophical hermeneutics method is used to analyze all the data that has been collected and studied in more depth with the perspective of Hindu ethics, Sapta Timira. Looking for the relationship between flexing behavior on Instagram users then connects it with Hindu ethics, especially the teachings of Sapta Timira, which is actually a supporter of flexing behavior.When a person is in the dark, flexing behavior can occur. This research resulted in the conclusion that digital social media, especially Instagram, is intended to facilitate access to information and communication. But unfortunately at this time, there are actually many negative impacts that occur. Digital social media has turned into a place for some users to show off. Of the many teachings of Hindu ethics, there is one concept that can describe the current condition of society, especially adolescents. The teaching is the teaching of Sapta Timira which means 7 darkness makes humans forget themselves. Some people understand the occurrence of flexing and then some others think that the current use of Instagram media is not wise. It is hoped that this research can help the public to understand related to flexing behavior considering that currently references related to flexing behavior are still minimal.